Optimization Of The Use Of Islamic Religious Education Laboratories In The Practice Of Participants' Worship Education At State Junior High School In Pangkajene District Pangkep Regency - Munawir Saharuddin; Hannani Hannani; Usman Noer; Hamdanah Said; Muliati Muliati; Samsinur Samsinur (International Forum of Researchers and Lecturers, 2025)
This study discusses the Optimization of the Use of Islamic Religious Education Laboratories in the Practice of Student Worship at State Junior High Schools in Pangkajene District, Pangkep Regency. The main problem is how the Islamic Religious Education Laboratory can be optimized as a facility and infrastructure that supports the development and progress of Islamic Religious Education. The author uses a research approach with qualitative methods in data collection, as well as testing and analyzing data qualitatively. The research paradigm is constructivism; data sources are Principals, PAI Teachers, Students (primary data) and documents related to the management of the PAI Laboratory (secondary data); The research instrument is the researcher himself and is assisted through data collection tools, namely observation guidesheets, interview guidelines and document study guidelines; Data collection techniques are participation observation, in-depth interviews, and documentation; and testing the validity of the research results applying source triangulation and triangulation techniques. The research was carried out in four State Junior High Schools in Pangkajene District, Pangkep Regency. The results of the study showed that 1) The condition of PAI laboratories in the schools studied varied in terms of availability and quality of facilities. All schools have PAI laboratories, but there are gaps in infrastructure and equipment due to differences in budget allocation. 2) Laboratory use of PAI showed variation in intensity and effectiveness. Some schools have integrated the use of laboratories into the curriculum, while others still face challenges in optimization. 3) The practice of students' worship varies in the level of consistency and understanding. The majority of students have awareness of the importance of worship, but the level of practice varies. 4) Factors that affect the use of PAI laboratories include the availability of infrastructure, teacher competence, budget allocation, school management, student motivation, and education policies. This study recommends increasing budgets, developing teacher competencies, integrating curriculum, collaboration between schools, utilizing technology, and periodic evaluations to optimize the use of PAI laboratories and improve students' practice of worship.